Internet interconnection infrastructure: Lessons from the global South - Fernanda R. Rosa (Internet Policy Review, 2021)
This article examines the formation of the first internet exchange point (IXP) in Mexico amid the implementation of telecommunication reforms and asymmetric regulations in a market with low level of competition. An IXP is defined as a shared interconnection facility and a key internet governance arena where players with myriad goals and functions mesh in interlaced technical and political dynamics. The study shows how data centres, passive infrastructure and autonomous system numbers play a critical role that stand out in the context of lack of infrastructure in Mexico. The paper argues that the challenges for an IXP to become stable in such a context in the global South is a result of IXP imagined affordances and the way that infrastructure, the telecommunications incumbent, its competitors, the state regulator, and the IXP operator interact, keeping the initiative in a fragile equilibrium.
Keywords: 300; Internet exchange point (IXP); Internet interconnection; Asymmetric Regulation; Mexico; Global South